2009
DOI: 10.1097/ajp.0b013e31817bcc78
|View full text |Cite
|
Sign up to set email alerts
|

How to Apply the ICF and ICF Core Sets for Low Back Pain

Abstract: The ICF is a promising new framework and classification to assess the impact of Low Back Pain. The ICF and practical tools, such as the ICF Core Sets for Low Back Pain, are useful for clinical practice, outcome and rehabilitation research, education, health statistics, and regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
1
26
0
4
Order By: Relevance
“…Tendo em vista que múltiplos aspetos da funcionalidade estavam comprometidos em algum grau, ficou evidenciada a necessidade de intervenções multiprofissionais no atendimento desses pacientes 11 , esse é um achado esperado nas afecções musculoesqueléticas crônicas 12 . A avaliação do impacto da lombalgia sobre a qualidade de vida desses pacientes com o QRM e o SF-36 mostrou, também, comprometimento em variados aspectos da funcionalidade dessas pessoas, reforçando a indicação da abordagem terapêutica multidisciplinar.…”
Section: Categoriaunclassified
“…Tendo em vista que múltiplos aspetos da funcionalidade estavam comprometidos em algum grau, ficou evidenciada a necessidade de intervenções multiprofissionais no atendimento desses pacientes 11 , esse é um achado esperado nas afecções musculoesqueléticas crônicas 12 . A avaliação do impacto da lombalgia sobre a qualidade de vida desses pacientes com o QRM e o SF-36 mostrou, também, comprometimento em variados aspectos da funcionalidade dessas pessoas, reforçando a indicação da abordagem terapêutica multidisciplinar.…”
Section: Categoriaunclassified
“…Each Core Set provides a selection of the most salient categories for a given condition or setting, consisting of as few categories as practically possible, but as many as necessary to encompass the typical spectrum of function (10). Consequently, the Core Sets, in particular, have been proposed as practical ICF-based clinical tools to guide the rehabilitation cycle (11).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, research is required to substantiate whether the LBP Core Sets are sufficiently comprehensive to reflect the tasks and actions that are important to patients and form the focus of their treatment (13,14). If this condition is met, the Core Sets may serve as a universal tool, in and of themselves, to guide the development, monitoring and evaluation of patient-generated goals during multidisciplinary rehabilitation (9,11). The current study was therefore designed to investigate whether the ICF LBP Core Sets were sufficient to cover the activities that patients with CLBP identify as difficult and prioritize as goals when commencing multidisciplinary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Stier-Jarmer et al (2006) concluded that ICF implementation on chronic low back pain (LBP) was a promising new framework. In another review by Roe et al (2013) the criticisms were towards psychosocial and environmental factors that were scarcely addressed.…”
Section: Disability and Chronic Pain 33mentioning
confidence: 99%